Trust in the police and the militarisation of law enforcement in Latin America - Sung, Hung-En (Comparing police organizations, 2024)
Modern civilian police in Latin America has transitioned from an authoritarian past to a violent present. This institutional trajectory has evolved in the shadow of recurrent attempts by elected civilians to bring the armed forces back to domestic politics for partisan or personal gains. Current militarisation of law enforcement is another exploitation of the traditional supremacy of the armed forces over the police, which could have important repercussions on citizen trust in the police. Survey data from 28,874 adults in 18 countries were analysed to identify patterns of trust in both the armed forces and the police and to assess the impact of public support for the militarisation of law enforcement on citizen trust in the police. Results suggest that although both the military and the police are in general moderately appreciated by the citizenry, when criminal violence and political instability strike, public trust in the two security institutions starts to move in opposite directions. Subregional differences notwithstanding, the arrival of armed forces as iron-fisted guardians preventing society’s descent into violent chaos amidst insecurity and chaos typically damages police legitimacy. Declining trust in the police and increasing public support for the militarisation of law enforcement feed a downward spiral in high-crime environments that further discredits the police. Political implications of this legitimacy crisis are discussed, and policy solutions are recommended.